UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN METODE PEMBELAJARAN MELALUI SUPERVISI KLINIS DI SLB NEGERI PEMBINA BLANGKEJEREN, GAYO LUES: UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN METODE PEMBELAJARAN MELALUI SUPERVISI KLINIS DI SLB NEGERI PEMBINA BLANGKEJEREN, GAYO LUES (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2020)
This article will explain the efforts to improve the ability of teachers in the use of learning methods through clinical supervision in the Extraordinary School (SLB) of Pembina Blangkejeran, Gayo Lues Regency. This action research uses a qualitative approach as a form of research that focuses on meaning through learning to observe people by interacting in a natural state by using three kinds of data collection methods, namely interviews, observation and documentation studies. Based on the results of the study it can be concluded that the implementation of school action research by implementing clinical supervision is needed as an effort in order to improve the ability of teachers to use learning methods, because it contains strategies so that students can learn effectively and accurately. Improving the ability of teachers to use learning methods through clinical supervision is one solution that is quite effective. This can be seen from the final results of the study where the teacher can master the existing indicators in determining learning methods and looking for methods that are truly appropriate and in accordance with the learning objectives and the conditions of the classroom environment and the school environment itself which further provides benefits for improving student learning achievement and improving the quality of learning in school.